INTERNALISASI NILAI NASIONALISME MELALUI KEARIFAN LOKAL KULINER: STUDI DESKRIPTIF PEMBELAJARAN TATA BOGA DI SMK BINA WISATA LEMBANG - Resti Megantari; Delila Kania; Asep Deni Normansyah (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study is motivated by the decline in students' sense of nationalism as a consequence of globalization, which has weakened appreciation for local culture, including Indonesian culinary heritage. This study aims to describe the internalization of nationalism values through the introduction of Indonesian culinary heritage in Culinary Arts learning, to identify the obstacles encountered, and to explain the efforts made to overcome them. A qualitative approach with a descriptive method was employed. The participants consisted of a Civics Education teacher, Culinary Arts teachers, the Head of the Culinary Arts Department, and eleventh-grade students at SMK Bina Wisata Lembang. Data were collected through interviews, observation, and documentation. The findings indicate that learning about Indonesian culinary heritage fosters students' pride, love for their homeland, and awareness of preserving national culture through both theoretical and practical activities. The main obstacles include students' limited prior knowledge of local cuisine and the stronger appeal of foreign culinary trends on social media. Teachers addressed these challenges through innovative media, cooking practice, project-based learning, and by integrating Pancasila values into every learning activity. Therefore, culinary learning grounded in local wisdom serves as an effective medium for internalizing nationalism values among vocational high school students.